The new Southeast Asian goblin spider genus Aposphragisma (Araneae, Oonopidae): diversity and phylogeny - Thoma, Marco; Kranz-Baltensperger, Yvonne; Kropf, Christian; Graber, Werner; Nentwig, Wolfgang; Frick, Holger (Zootaxa, 2014)
The new genus Aposphragisma (Araneae, Oonopidae, Oonopinae) comprising the new species A. baltenspergerae, A. borgulai, A. brunomanseri, A. confluens, A. dayak, A. dentatum, A. draconigenum, A. hausammannae, A. helvetiorum, A. kolleri, A. menzi, A. monoceros, A. nocturnum, A. retifer, A. rimba, A. salewskii, A. scimitar, A. sepilok and A. stannum is described. It is characterised by very hard bodied, strongly sclerotized species with completely armoured prosoma and strongly sclerotized ventral and dorsal abdominal scuta. Aposphragisma gen. nov. is placed within the Gamasomorpha-group sensu Saaristo (2001). Descriptions and illustrations are given for all new species. A phylogenetic analysis based on 40 characters using Prethopalpus fosuma, Gamasomorpha asterobothros, G. cataphracta, G. seximpressa, Xestaspis biflocci, X. kandy and X. paulina as outgroup-taxa and Cortestina thaleri (Oonopidae, Sulsulinae) as the root is presented and discussed. Furthermore it is shown that females of Aposphragisma gen. nov. possess complex internal genitalia. The members of the new genus are ground-dwelling litter inhabitants restricted to Southeast Asian lowland and montane forests, with more than 60% of the species only known from single localities. They are presumed to be negatively affected by the massive destruction of pristine forest habitats within their range. This work has been conducted within the framework of the Planetary Biodiversity Inventory (PBI) of Oonopidae (see http://research.amnh.org/oonopidae).